Review Deskriptif Buku Teori Kepribadian (Theories Of Personality) Edisi 7, Buku 2 Karya: Jess Feist & Gregory J. Feist - Azizah, Neng Astri; Yustiana, Yusi Riksa (Sinergi : Jurnal Ilmiah Multidisiplin, 2025)
This descriptive review aims to critically examine the book "Theories of Personality, 7th Edition, Book 2" by Jess Feist and Gregory J. Feist, a fundamental literature in the study of psychology and mental health services. This analysis dissects the book's theoretical scope, focusing on humanistic, trait, and social-cognitive approaches. The book's primary strengths lie in its ability to present a balance between various perspectives, integrate contemporary research from neuroscience and genetics, and utilize a systematic pedagogical architecture that facilitates learning. However, a key limitation is identified, namely a Western epistemological bias that necessitates critical contextualization and adaptation when applied within the Indonesian sociocultural landscape. In conclusion, this book is an essential resource for students and practitioners of guidance and counseling in Indonesia, providing a solid theoretical foundation for case conceptualization, intervention planning, and professional competency development.   Review deskriptif ini bertujuan untuk mengkaji secara kritis buku "Teori Kepribadian Edisi 7, Buku 2" karya Jess Feist dan Gregory J. Feist, sebuah literatur fundamental dalam studi psikologi dan layanan kesehatan mental. Analisis ini membedah cakupan teoretis buku yang berfokus pada aliran humanistik, trait, dan kognitif-sosial. Kekuatan utama buku ini terletak pada kemampuannya menyajikan keseimbangan antara berbagai perspektif, integrasi riset kontemporer dari neurosains dan genetika, serta arsitektur pedagogis yang sistematis untuk memfasilitasi pembelajaran. Meskipun demikian, diidentifikasi pula keterbatasan utama, yakni bias epistemologis Barat yang menuntut adanya kontekstualisasi dan adaptasi kritis saat diaplikasikan dalam lanskap sosiokultural Indonesia. Kesimpulannya, buku ini merupakan sumber daya esensial bagi mahasiswa dan praktisi bimbingan dan konseling di Indonesia, menyediakan landasan teoretis yang kokoh untuk konseptualisasi kasus, perencanaan intervensi, dan pengembangan kompetensi profesional.